Characterization of Activated Charcoal Produced Using Green Chemistry Principle Approach Number 7 - Thohir, Muhammad Bakhru; Wijaya, Terry Esi Putri (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Charcoal is an important component in the effort to provide clean water. One of the water qualities that need to be considered is the level of hardness. Reducing the level of hardness can be done with activated charcoal. The production of activated charcoal uses many synthetic materials. Therefore, aim of research is to produce, test the performance, and characterization of activated charcoal made with natural acids. The stages of this research are charcoal preparation and natural acid activator, carbonization, activation with natural acids (Averrhoa bilimbi L. and Citrus aurantifolia S.), and characterization. The production results were tested for adsorbing ability and characterization using FTIR, SEM, and XRD to determine the functional groups, structure, and components. The results showed that activated charcoal produced using natural acids had better performance in adsorbing. Characterization with FTIR showed the absorption of C-H functional groups shown at 785 cm-1, 1100 cm-1 for C-O functional groups, 3368 cm-1 for O-H stretching vibration groups. Typical active charcoal groups were also detected at wave numbers 1704 cm-1for C=O functional groups and 1575 cm-1 for C=C groups. Characterization with XRD showed the same pattern between charcoal produced with natural acids and the control. SEM images showed clear pores on the surface of the activated charcoal. Thus, natural acids can really be a candidate for activator replacement in the production of activated charcoal that applies the principles of green chemistry.